2015
DOI: 10.1124/jpet.114.221226
|View full text |Cite
|
Sign up to set email alerts
|

A Novel In Vivo Receptor Occupancy Methodology for the Glucocorticoid Receptor: Toward An Improved Understanding of Lung Pharmacokinetic/Pharmacodynamic Relationships

Abstract: Investigation of pharmacokinetic/pharmacodynamic (PK/PD) relationships for inhaled drugs is challenging because of the limited possibilities of measuring tissue exposure and target engagement in the lung. The aim of this study was to develop a methodology for measuring receptor occupancy in vivo in the rat for the glucocorticoid receptor (GR) to allow more informative inhalation PK/PD studies. From AstraZeneca's chemical library ofpropoxy]indazol-1-yl]-N-methyl-benzamide] was identified to have properties that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Rats were anesthetized at the time of sampling [time points, 2 and 30 minutes, were chosen based on a previously published study (5) ] with isoflurane (FORENE Ò ; Abbott Scandinavia AB, Solna, Sweden), and a terminal blood sample was collected as previously described (23) to isolate plasma and stored at -20°C until analysis. The heart and lungs were removed from the thorax en bloc.…”
Section: Drug Administration and Tissue Collectionmentioning
confidence: 99%
“…Rats were anesthetized at the time of sampling [time points, 2 and 30 minutes, were chosen based on a previously published study (5) ] with isoflurane (FORENE Ò ; Abbott Scandinavia AB, Solna, Sweden), and a terminal blood sample was collected as previously described (23) to isolate plasma and stored at -20°C until analysis. The heart and lungs were removed from the thorax en bloc.…”
Section: Drug Administration and Tissue Collectionmentioning
confidence: 99%
“…In fact, there are no experimental methodologies available to do this, although indirect approaches such as target occupancy have been employed. (3,5) The inability to define the target site concentration(s) of inhaled drug even in preclinical species clearly poses a huge challenge for developing inhaled drug treatments with the objective of optimizing drug potency and targeting of relevant lung structures. Currently used methodologies to evaluate inhaled drug pharmacology and predicting therapeutic dosing in man seem to still largely depend on doseresponse studies in preclinical species with functional readouts at the level of the lung as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Information about serum concentrations of GCs and receptor occupancy in relevant target cells for different doses should be useful in predicting the lowest doses required for efficacy with minimal side-effects, but such information is not readily available in the literature. However, a recent study in mice showed no correlation between receptor occupancy and serum GC concentrations (Boger et al, 2015). This study also established that a GC dose of 47nmol/kg was required to occupy 50% of receptor and that more of the receptor was occupied at higher doses.…”
Section: Introductionmentioning
confidence: 99%